Huellas de la memoria: Testimonio de Nancy Morejón. - CORDONES-COOK, JUANAMARÍA (Revista de Estudios Hispánicos, 2025)
The text focuses on the literary testimony "Traces of Memory" by the Cuban poet Nancy Morejón, a prominent figure in contemporary Afro-Cuban literature. This testimony, the result of more than thirty years of interviews and dialogues, documents aspects of Cuban and Caribbean cultural reality from the perspective of an authoritative and cultured voice, who has been both a protagonist and witness of important historical and cultural processes. The work falls within the testimonial genre, which combines elements of oral history, autobiography, and ethnography, and reflects both personal and collective memory, mediated by the subjectivity of the author and the curator of the testimony. Additionally, the text contextualizes Morejón’s career within the framework of the Black Renaissance in Havana, a cultural phenomenon that emerged after the Cuban Revolution of 1959 and promoted the visibility and development of Afro-descendant intellectuals in various artistic and academic disciplines.